2017
DOI: 10.1111/obr.12630
|View full text |Cite
|
Sign up to set email alerts
|

Oleoylethanolamide: The role of a bioactive lipid amide in modulating eating behaviour

Abstract: Fatty acid ethanolamides are lipid mediators that regulate a plethora of physiological functions. One such bioactive lipid mediator, oleoylethanolamide (OEA), is a potent agonist of the peroxisome proliferator-activated receptor-alpha (PPAR-α), which modulates increased expression of the fatty acid translocase CD36 that enables the regulation of feeding behaviour. Consumption of dietary fat rich in oleic acid activates taste receptors in the gut activating specific enzymes that lead to the formation of OEA. OE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 235 publications
(365 reference statements)
0
55
0
Order By: Relevance
“…46 In contrast, OEA increases the latency to feed, and thus, mediates the hypophagic effects. 4,6 This finding illustrated that the injection of OEA in free-feeding mice or rats elevated the feeding latency with no effect on meal size, while a delay in the onset of feeding as well as a reduction in meal size was reported with OEA administration in food-deprived animals. 42 Overall, the best action of OEA, which increases the feeding latency, makes it a novel satietyenhancing product.…”
Section: Impact Of Oleoylethanolamide On Latency To Feedmentioning
confidence: 75%
See 4 more Smart Citations
“…46 In contrast, OEA increases the latency to feed, and thus, mediates the hypophagic effects. 4,6 This finding illustrated that the injection of OEA in free-feeding mice or rats elevated the feeding latency with no effect on meal size, while a delay in the onset of feeding as well as a reduction in meal size was reported with OEA administration in food-deprived animals. 42 Overall, the best action of OEA, which increases the feeding latency, makes it a novel satietyenhancing product.…”
Section: Impact Of Oleoylethanolamide On Latency To Feedmentioning
confidence: 75%
“…These events related to taste recognition are regulated by signalling pathways, which are activated through the binding of long‐chain fatty acids to CD36 . Numerous studies performed on both humans and rodents indicated that CD36, a scavenger receptor expressed in multiple cell types, plays a critical role in mitochondrial fatty acid oxidation in skeletal muscle, and CD36 functions in regulating mitochondrial fatty acid oxidation along with carnitine palmitoyltransferase‐1 (CPT1), a protein that is responsible for the translocation of fatty acids from the cytosol to the mitochondrial matrix, where fatty acid oxidation occurs . In addition, some studies conducted on CD36‐deficient mice have reported defective fatty acid uptake, and thus disorders in fatty acid metabolism .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations